Canine non-hematopoietic gastric neoplasia - von Babo, V.; Eberle, N.; Mischke, R.; Meyer-Lindenberg, A.; Hewicker-Trautwein, M.; Nolte, I.; Betz, D. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
Objective: Aim of this study was to investigate epidemiologic and diagnostic characteristics of canine non-hematopoietic gastric neoplasia and to evaluate the surgical outcome of selected cases.Material and methods: Patient data of dogs with histologically confirmed nonhematopoietic gastric tumors were reviewed and dogs with surgical intervention were followed up.Results: 38 dogs were included into the evaluation. Histopathologic diagnoses comprised carcinoma/adeno- carcinoma (n = 33), gastrointestinal stromal tumor (GIST) (n = 4), and leiomyoma (n = 1). Patients’ median age was 10 years, median weight was 20 kg and the male:female ratio was 1.4 : 1.The breeds represented by most individuals were Chow Chow, Collie, Hovawart and mixedbreed. Most frequent presenting complaint was vomiting. Only a low proportion of dogs were presented with anemia, thrombocytopenia or hypoproteinemia. In 58% of cases, ultrasonographic examination led to findings that were considered compatible with gastric neoplasia. Gastric wall thickening and loss of layering were the most common sonographic findings. Most frequent endoscopic findings were mucosal thickening and reddening; ulcerations were infrequent. Computed tomography findings were compatible with gastric neoplasia in two cases in which CT was performed. Intra-operative cytology results showed accordance with histologic diagnoses in 88% of cases. Five dogs with different underlying pathology and variable disease extension underwent surgical tumor resection. In one patient, recurrence was diagnosed after 104 days. Survival times of these dogs ranged between 7 and 2326 days.Conclusion and clinical relevance: Ultrasonography and, in selected cases, computed tomography aided in the diagnosis of gastric neoplasia. Intra-operative cytology possessed diagnostic value. In cases in which surgical resection was attempted, survival times varied markedly likely due to variable disease extension and underlying pathology (e. g. adenocarcinoma versus leiomyoma).
Keywords: Stomach; tumor; cytology; surgery; survival